Reconsolidation or extinction: Transcription factor switch in the determination of memory course after retrieval - de la Fuente, V. (2011)
In fear conditioning, aversive stimuli are readily associated with contextual features. A brief reexposure to the training context causes fear memory reconsolidation, whereas a prolonged re exposure induces memory extinction. The regulation of hippocampal gene expression plays akey role in contextual memory consolidation and reconsolidation. However, the mechanisms that determine whether memory will reconsolidate or extinguish are not known. Here, we demonstrate opposing roles for two evolutionarily related transcription factors in the mouse hippocampus. We found that nuclear factor-KB (NF-kB) is required for fear memory reconsolidation. Conversely, calcineurin phosphatase inhibited NF-kB and induced nuclear factor of activated T-cells (NFAT) nuclear translocation in the transition between reconsolidation and extinction. Accordingly, the hippocampal inhibition of both calcineurin and NFAT independently impaired memory extinction, whereas inhibition of NF-kB enhanced memory extinction. These findings represent the first insight into the molecular mechanisms that determine memory reprocessing after retrieval, supporting a transcriptional switch that directs memory toward reconsolidation or extinction. The precise molecular characterization of postretrieval processes has potential importance to the development of therapeutic strategies for fear memory disorders. © 2011 the authors.